2007
DOI: 10.3354/meps07004
|View full text |Cite
|
Sign up to set email alerts
|

Response and recovery dynamics of seagrasses Thalassia testudinum and Syringodium filiforme and macroalgae in experimental motor vessel disturbances

Abstract: Shallow seagrass beds worldwide are being negatively impacted by human activities. Damage by boats includes anchor scars, propeller scars, and hull groundings. In some Thalassia testudinum-dominated systems, vessel damage may persist for years or decades, and even small scars may leave seagrass habitat susceptible to severe erosion by wind and wave-driven currents and storms. Cost-effective techniques for restoration in these erosion-prone systems must include sediment replacement and stabilization to best enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 38 publications
(46 reference statements)
3
37
0
Order By: Relevance
“…The recovery from three months of light reduction is faster than has previously been reported for larger seagrass species. Generally, recovery in these species takes years, decades or has been predicted to take centuries (Boese et al, 2009;Bryars and Neverauskas, 2004;Collier et al, 2009;Gonzalez-Correa et al, 2005;Hammerstrom et al, 2007;Neckles et al, 2005). Interestingly, this relatively fast recovery occurred despite up to 72% loss of leaf biomass, highlighting the fast leaf production rates of Amphibolis compared to other large seagrasses (Marba and Walker, 1999), and high recovery potential if actively growing clusters (up to 42%) remain on the stem from which new leaves can form.…”
Section: Timescales Of Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery from three months of light reduction is faster than has previously been reported for larger seagrass species. Generally, recovery in these species takes years, decades or has been predicted to take centuries (Boese et al, 2009;Bryars and Neverauskas, 2004;Collier et al, 2009;Gonzalez-Correa et al, 2005;Hammerstrom et al, 2007;Neckles et al, 2005). Interestingly, this relatively fast recovery occurred despite up to 72% loss of leaf biomass, highlighting the fast leaf production rates of Amphibolis compared to other large seagrasses (Marba and Walker, 1999), and high recovery potential if actively growing clusters (up to 42%) remain on the stem from which new leaves can form.…”
Section: Timescales Of Recoverymentioning
confidence: 99%
“…A key concern in assessing the impact of dredging on seagrass ecosystems is the length of time these ecosystem functions are compromised, that is, how long does it take for the ecosystem to recover. Recovery from dredging related stressors, defined as a return to predisturbance or undisturbed conditions (Elliott et al, 2007) has been demonstrated (Biber et al, 2009;Collier et al, 2009;Gonzalez-Correa et al, 2005;Hammerstrom et al, 2007), and the rate of recovery depends on a variety of factors (see Pickett and White, 1985) such as the size and severity of the impact (Fonseca et al, 2004) and the seagrass species. Recovery can take years and, in some instances, has been predicted to take centuries (Walker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Further, turbulence and wakes from recreational boats and ferries damage aquatic vegetation (Ali et al 1999;Asplund 2000;Doyle 2001;Eriksson et al 2004;Sandström et al 2005) and thereby reduce populations of fish that depend on this vegetation (Sandström et al 2005), and alter macroinvertebrate communities (Bishop 2007). In very shallow water, propeller scarring may be important (e.g., Asplund 2000; Burfeind and Stunz 2006;Hammerstrom et al 2007). Recreational watercraft (small outboards and personal watercraft) may disturb animals using the shore zone (Asplund 2000;Rodgers and Schwikert 2002;Stolen 2003) and produce pollution as well (Lico 2004).…”
Section: Recreational Activitiesmentioning
confidence: 99%
“…These incidents create specific types of injuries, including blowholes, propeller scars, and berms that can excavate sediment, destroy above-and belowground seagrass biomass, and/or bury seagrasses. Natural recovery of seagrass communities from severe disturbance such vessel grounding blowholes is a slow process, and recovery of deep excavations may take several years to over a decade (Zieman 1976;Durako et al 1992;Dawes et al 1997;Kenworthy et al 2002;Hammerstrom et al 2007;Di Carlo & Kenworthy 2008). …”
Section: List Of Tablesmentioning
confidence: 99%
“…For example, placing sediment fill into excavations is intended to stabilize sites from erosion and recreate the physical matrix that supports seagrasses and ecosystem functioning (Hammerstrom et al 2007). Because seagrasses ecosystems are often nutrient-limited (Short 1987;Fourqurean et al 1992a), applying fertilizer serves to reestablish or augment pools of vital nutrients that may be limiting to seagrass growth (Kenworthy et al 2000).…”
Section: List Of Tablesmentioning
confidence: 99%